Cultural and Value Differences of Goddess in Ancient Greece and China - Sheng, Xiaomin (European Scientific Journal, ESJ, 2017)
Ancient Chinese and Greek mythology are regarded as two wonders in the world history of literature. In Chinese ancient mythology and ancient Greek mythology, the image of the goddess with its romantic love story and rich image-building has become a hot research topic. Goddess originally means superior female immortals with unattainable qualities in ancient mythology. Unlike today, the implication of goddess is extended, referring to the women with good temperament and outstanding in real life, they are the object of men’s admiration and women’s imitation. Different people define their own favorite goddess based on their unique aesthetic standards, the term ‘goddess’ is widely used in the present day, and it has become a hot topic in pop culture. This paper analyzes and compares the images of goddess in ancient Chinese and Greek mythology literature from four aspects: quantities, image-building, historical responsibility and status, and attitudes towards love and sexual relations. And then compared the different images of ‘goddess’ between ancient and nowadays, to understand the goddess images of ancient mythology literature and the cultural connotations inhered by goddess images, relate it to the right, culture and state towards women nowadays, to study their impact on Chinese and Greek society. Through the analysis of goddess images of ancient Chinese and Greek literature, to evaluate their impact in shaping the Western culture, national identity, values and other aspects of value orientation.